PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 031 BANJAR XII - Teti Diana; Otang Kurniaman; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was aimed to increase students achievement of sains lesson in IV grade year of 2014/2015. The subject of this research in students IV grade of state Elementary School 031 Banjar XII which is total of 18 students, consisted of 10 girls and 8 boys. This was a classroom research which has two cycles which was conducted on March 17th to April 21th 2015. The data shown that either learning process or students achievement increased. This was found from students and teachers scores in learning process increased. First cycle at the first meeting teacher’s activity was 66,7%categorized as good and increased 8,3% at the second meeting as 75% categorized as good. Meanwhile at the second cycle at the first meeting the percentage of teacher’s activity increased as 87,5% categorized as very good and in the second meeting it increased as 8,3% so the percentage became 95,8% categorized as very good. While students activities in learning process also increased. At the first cycle in the first meeting, the percentage of students activities was 62,5% categorized as good and the second meeting it increased as 8,3% so became 70,8% categorized as good. At the second cycle in the first meeting it increased to 83,3% categorized as very good. At the second meeting the percentage of students’ activities increased as 8,4% became 91,7% categorized as very good. However, students’ achievement also increased. The basic score of daily examination as 6,73% which 11 students passed and 7 students failed. The ending of daily examination was 61,11% and the average 70,56 on the passing grade. The second daily examination also increased from basic score of as 11,01% which 15 students passed and 3 students failed. The ending of second daily examination was 83,33% and the average was 78,33. Based on the explanation above it can be concluded that the implementation cooperative learning make a match thype to increase students achievement in social lesson of students IV grade of State Elementary School 031 Banjar XII.Key Words : Cooperative Learning Make A Match Thype, Sains Lesson Learning Outcomes